Cooperative and Decentralized Decision-Making for Loyal Wingman UAVs - Giacomossi, Luiz; Dias, Stiven Schwanz; Brancalion, José Fernando; Maximo, Marcos R. O. A. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2021: Anais do XIII Simpósio Brasileiro de Robótica e XVIII Simpósio Latino Americano de Robótica, 2021)
With the application of decision-making techniques, it is possible to automate many of the intelligent decisions of UAVs, leaving human commanders to focus on higher-level decisions in modern warfare scenarios, providing a crucial tactical advantage. This paper applies key methods to enable decentralized decision-making for autonomous combat UAVs, also known as loyal wingman (LW) drones. A simulator was developed to simulate to implement and analyze the behaviors of the so-called LW. We used as the main decision-making technique the construction of a behavior tree (BT) capable of providing decisions in a decentralized manner, and for parameters optimization, the PSO optimization algorithm was used. Our approach shows a promising result of threat elimination efficiency of approximately 93%.